Pedagogical Mechanisms for the Development of a Culture of Communication Between Students of Technical Universities (Eurasian Journal of Learning and Academic Teaching, 2022)
This article discusses the spontaneous and purposeful transfer of knowledge and experience of students in socio-cultural time and space due to communicative processes in the development of the communicative culture of students of technical universities. Broadcasting is a special type, which means ensuring the historical and cultural continuity of knowledge and experience, the process of timely transmission of cultural information is more complex than synchronous communication, which combines the features of communication and automation, changing the context of information perception